Intensified treatment of hyperphosphatemia associated with reduction in parathyroid hormone in patients on maintenance hemodialysis - Chen, Lan (Ren Fail, 2018)
Background: This study investigated the therapeutic effect of intensive phosphorus-lowering therapy on intact-parathyroid hormone (iPTH) levels in hemodialysis patients. Methods: Ninety-five hemodialysis patients with serum phosphorus ≥1.78 mmol/L and iPTH ≥300 pg/dL were apportioned to either the treatment or control group (n = 43 and 52, respectively) based on patient commitment to treatment. The treatment group was given phosphorus-lowering therapies with phosphate binders (lanthanum, sevelamer or/and calcium reagent) combined with dietary phosphate restriction and intensified hemodialysis. The control individuals were given low doses of calcium agents, if serum calcium was <2.54 mmol/L. Percent changes in serum phosphorus and iPTH levels were compared between the two groups. In addition, based on the time required to achieve >20% decrease in serum phosphorus, the patients in the treatment group were further stratified as rapid responders (≤2 months; 27 patients) or slow responders (>2 months; 16 patients) and percent changes in iPTH were compared. Results: Serum phosphorus and iPTH levels decreased from baseline in the treatment group (−24.08 ± 1.93% and −9.92 ± 3.70%, respectively) but increased in the control group (22.00 ± 3.63% and 104.21 ± 23.89%; both p < .001). In the rapid responders subgroup, the iPTH decreased (−16.93 ± 3.49%), but in the slow responders subgroup the iPTH increased slightly (0.68 ± 7.37%, p < .05). Conclusions: For these patients on maintenance hemodialysis, intensive treatment of hyperphosphatemia was associated with a decrease in iPTH levels, especially for those who had achieved substantial reduction in serum phosphorus within 2 months.